Abrasivity characteristics of rocks from India and Nepal - Karki, Kiran (Journal of Nepal Geological Society, 1995)
Over the years, many attempts have been made to define and characterise rock abrasiveness. However, it is found that abrasiveness of rocks is not only difficult to define but also hard to measure. A number of relative rock abrasiveness tests have emerged but their results do not always faithfully reflect the characteristics of the rocks that may be useful in the excavation process. Under the circumstances, an in depth study of rock abrasiveness is warranted. The present study may provide additional help to fill a gap in this area. The study has addressed a number of issues on abrasivity of rocks and the objectives included inter-alia the following: 1. Developing and standardising appropriate testing techniques for evaluation of the abrasiveness and microhardness of the mine rocks. 2. Evaluating the abrasivity characteristics of mine rocks from Mosaboni copper mine, Jhinkpani limestone quarry and Indian coal-measure strata, Jharia, all from the Bihar State of India. 3. Evaluating the characteristics of a suite of rocks from Nepal (limestone from Nigale and quartzite from Bhedetar, Dhankuta District, Nepal). In this study a number of testing methods have been used to evaluate rock abrasiveness of rocks, specially the Cerchar Abrasivity Index (CAI), Schimazek Index and Indian School of Mines Abrasivity Test (ISMAT). The tests were performed in the rock mechanics laboratory of Indian School of Mines (ISM), Dhanbad, India. The results of these tests are discussed in detail. Hopefully, this study on abrasivity characteristics of rocks will aid in the selection of appropriate tools and excavation systems thereby enhancing the work performances and reducing the costs in excavations.